(untitled) (Proceedings of Southern Federal University. Philology, 2014)
Inner monologue, as well as the usual oral monologue, bears reflection on any problem, often severe, intractable. The contents of the internal monologue can be addressed to the past, which evaluates, analyzes, discloses the true attitude to things, and to the future, dreams, suggestions and plans. Considering depressing speech it can be noted that it is inherent in the internal monologue of a depressive character. Considering it we can note that the factor of depression, respectively, affect the semantic and syntactic features of the inner monologue, it is not a “pure” autocommunication and should be understood not only to the characters but also to the reader. Analyzing the types and functions of inner monologue it is differentiated the following subtypes: inclusion, inner monologue and stream of consciousness. Basic identifiers of emotive vocabulary convey a general idea of the lexical field of emotions the characters in the novels of Spanish writers, feelings, emotions as particularly psychic reality. They form the lexical field of emotions of the characters. These identifiers are the emotions of fear, anxiety, depression, oppression, fear, aggression. Key words: inner monologue, autocommunication, dialogue, narrator, improperly direct speech.